Barbados : Fifth Review Under the Extended Arrangement, Request for Waiver of Nonobservance of Performance Criterion, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Barbados. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2021)
Barbados has made good progress in implementing its Economic Recovery and Transformation (BERT) plan to restore fiscal and debt sustainability, rebuild reserves, and increase growth. International reserves have increased to USD 1.3 billion at end-March 2021, supported by IFI loans. This, and a successful 2018-19 public debt restructuring, have helped rebuild confidence in the country's macroeconomic framework. However, a virtual standstill in the tourism sector during the pandemic took a significant toll in 2020, with the economy contracting by 18 percent. While Barbados was successful in containing the outbreak during 2020, a surge in COVID-19 cases in early 2021 resulted in the country's second national lockdown in February. Economic growth is projected at 3 percent for 2021 premised on a modest recovery of tourism in the second half of the year, but the outlook remains highly uncertain, and risks are elevated, also in light of the possible impact of recent volcanic activity in neighboring Saint Vincent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Barbados